A STUDY OF SMALL FARM RESERVOIRS FOR DEVELOPING SUSTAINABLE AGRICULTURE IN RAINFED AREAS - Sahu, R.K.; Singh, A.; Bhattacharya, A.K.; Singh, R.P. (Journal of Soil and Water Conservation, 2022)
Lack of water at times of need is the dominating constraint to increasing productivity in most of the rainfed areas. Small Farm Reservoir (SFR) can play an important ?tile in alleviating drought in these areas. Research on these storage systems have been conducted in Bangladesh, India, Philippines and Indonesia to determine their value in conserving rainwater, improving land productivity and the impact on fanner’s income. An SFR generally has individual ownership and covers a small part of the total area. Therefore, SFR can be managed easily by the farm owner with very little social problem. It has multiple potential uses such as reducing drainage congestion, irrigation and aquaculture with improved cropping systems using SFR. productivity and income can be increased, idle farm labours can be harnessed and faint family nutrition can be improved. The full use of SFR depends on innovativeness of the owner. Research work done on SFR at various places and their results have been reviewed in this paper.